Targeting regulation of the tumour microenvironment induces apoptosis of breast cancer cells by an affinity hemoperfusion adsorbent. Issue 1 (1st January 2021) - Wang, Lichun; Chen, Jian; Chai, Yamin; Han, Wenyan; Shen, Jie; Li, Nan; Lu, Jinyan; Du, Yunzheng; Liu, Zhuang; Yu, Yameng; Dong, Jingzhe; Ou, Lailiang
Abstract: The cytokine network of tumour microenvironment (TME) plays an important role in cancer growth and progression. The current work aims to provide a new strategy for cancer therapy based on the targeted regulation of cytokines in the TME. Here, heparin-coupled polyvinyl alcohol (PVA-H) microspheres have been developed as an adsorbent for selectively remove tumour-induced immunosuppressive cytokines, such as vascular endothelial growth factor (VEGF) and transforming growth factor-beta (TGF-β), but not tumour necrosis factor-alpha (TNF-α) which has an immune-stimulating effect and can inhibit tumour growth. The proliferation and apoptosis of breast cancer cells after perfusion were tested by cell viability assays, flow cytometry analysis and mRNA microarray assays. Results showed that the PVA-H microspheres efficiently absorbed the majority of VEGF (74.39%) and TGF-β (86.39%), but much less TNF-α (4.16%). The regulation of the cytokines had remarkable anti-proliferative and pro-apoptotic effects on breast cancer cells, which was further confirmed from the change of mRNA expression levels. Thus, targeting regulatory pathways within the TME by an affinity adsorbent that selectively depletes immunosuppressive cytokines is potentially a new and promising strategy for cancer therapy.